Chronic CD27-CD70 costimulation promotes type 1-specific polarization of effector Tregs - Bowakim-Anta, Natalia; Acolty, Valérie; Azouz, Abdulkader; Yagita, Hideo; Leo, Oberdan; Goriely, Stanislas; Oldenhove, Guillaume; Moser, Muriel (Frontiers in Immunology, 2023)
Most T lymphocytes, including regulatory T cells, express the CD27 costimulatory receptor in steady state conditions. There is evidence that CD27 engagement on conventional T lymphocytes favors the development of Th1 and cytotoxic responses in mice and humans, but the impact on the regulatory lineage is unknown. In this report, we examined the effect of constitutive CD27 engagement on both regulatory and conventional CD4+ T cells in vivo, in the absence of intentional antigenic stimulation. Our data show that both T cell subsets convert into type 1 Tconvs and Tregs, characterized by cell activation, cytokine production, response to IFN- and CXCR3-dependent migration to inflammatory sites. Transfer experiments suggest that CD27 engagement triggers Treg activation in a cell autonomous fashion. We conclude that CD27 may regulate the development of Th1 immunity in peripheral tissues as well as the subsequent switch of the effector response into long-term memory.